2022
DOI: 10.2147/ijn.s355142
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Gold Nanoparticles in Cancer Diagnosis and Treatment

Abstract: Cancer is the second leading cause of death in the world, behind only cardiovascular diseases, and is one of the most serious diseases threatening human health nowadays. Cancer patients’ lives are being extended by the use of contemporary medical technologies, such as surgery, radiotherapy, and chemotherapy. However, these treatments are not always effective in extending cancer patients’ lives. Simultaneously, these approaches are often accompanied with a series of negative consequences, such as the occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 190 publications
(197 reference statements)
0
57
0
1
Order By: Relevance
“…It is well-known that GNPs have a surface plasmon resonance (SPR) effect, which is the coherent oscillation of free electrons on the GNP’s surface, triggered by lights and energy [ 41 ]. Due to this property, many researchers reported that the combinational treatment of GNPs with various kinds of biomedical techniques such as lasers [ 42 ], radiations [ 43 , 44 ] and ultrasonics [ 45 ] can kill cancer cells by inducing necrosis and apoptosis of cancer cells depending on the size of the GNPs and the power of the GNP stimulating techniques they used [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that GNPs have a surface plasmon resonance (SPR) effect, which is the coherent oscillation of free electrons on the GNP’s surface, triggered by lights and energy [ 41 ]. Due to this property, many researchers reported that the combinational treatment of GNPs with various kinds of biomedical techniques such as lasers [ 42 ], radiations [ 43 , 44 ] and ultrasonics [ 45 ] can kill cancer cells by inducing necrosis and apoptosis of cancer cells depending on the size of the GNPs and the power of the GNP stimulating techniques they used [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the current results of research on AuNPs in cancer field are indeed encouraging, to the best of our knowledge, clinical applications of AuNPs in oncology are almost absent: as reported in the introductory section, only a few examples are in clinical trials, mainly on AuNPs as PTTs and delivery agents [ 41 , 42 , 43 , 44 ]. Unfortunately, the toxicity profile of AuNPs and other many factors, including the clearance of the mononuclear phagocytic system (MPS), the renal excretion, the physiological barriers, and the differences between patients decelerate clinical entering of the AuNPs [ 12 , 13 , 45 ]. The reader interested in the physical and chemical properties of AuNPs exploited in the field of oncology can consult the recent review by Bai et al [ 13 ].…”
Section: The Application Of Aunps In Oncologymentioning
confidence: 99%
“…Therefore, there is an urgent need for more in-depth studies to clarify and research the factors influencing the pharmacokinetics, biodistribution and in vivo toxicity of AuNPs. However, determining which parameters are most important in the in vivo toxicity and biodistribution of AuNPs is very challenging for many reasons: (i) the available publications differ widely in experimental methods and conditions (differences in exposure time and dose [ 12 ] and route of administration [ 151 , 154 ]; (ii) species-specific differences in reactions and sensitivity [ 155 ]; (iii) the limitations of current pre-clinical models (testing the toxicity of AuNPs in conventional 2D models may not accurately reflect the AuNPs-cell interaction) [ 156 ]. Another challenge concerns ligands used for the functionalization of AuNPs.…”
Section: Challenges Of the Application Of Aunps In Cancer Treatmentmentioning
confidence: 99%
See 2 more Smart Citations